HEALTH STATUS AND DISEASE PATTERNS AMONG WORKERS IN PLASTIC MATERIAL MANUFACTURING COMPANIES IN HUNG YEN, 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to describe the current health status and disease burden among workers at plastic material manufacturing companies in Hung Yen in 2024.Methods: A cross-sectional descriptive study was conducted on 853 workers at plastic material manufacturing companies in Hung Yen. Data were collected retrospectively from the workers’ health records in 2024.Results: Most workers were male (78.8%) and aged 30–39 years (39.3%). The rate of underweight workers was 6.9%, while overweight and obesity accounted for 40.9%. Workers with good health status (type I and II) made up 70.4%, whereas poor health status (type IV and V) accounted for 7.3% and 0.8%, respectively. The most common diseases were digestive disorders (53.5%), ear-nose-throat diseases (49.5%), and endocrine disorders (49.5%). Workers with two diseases accounted for the highest proportion (30.7%), with a significant difference in disease number between males and females (p
Keywords: Plastic materials, health, workers, Hung Yen.